The clinical associations with cardiomegaly in patients undergoing evaluation for pulmonary hypertension - Benjamin Daines; Sanjana Rao; Omid Hosseini; Sofia Prieto; John Abdelmalek; Mohamed Elmassry; Pooja Sethi; Victor Test; Kenneth Nugent (Greater Baltimore Medical Center, 2021)
Background Chest radiographs can identify important abnormalities in patients undergoing diagnostic evaluation for cardiovascular diseases. Cardiomegaly often reflects cardiac chamber dilation, or cardiac muscle hypertrophy, or both conditions. The clinical implications of cardiomegaly depend on the underlying clinical disorder. Does cardiomegaly have any clinical, laboratory, echocardiographic, and right heart catheterization associations in patients undergoing evaluation for pulmonary hypertension? Methods Patients referred to a pulmonary vascular disease clinic for possible pulmonary hypertension underwent a comprehensive evaluation that included right heart catheterization. These patients also had chest radiographs, laboratory studies, and echocardiograms. The patients were divided into two groups based on the presence or absence of cardiomegaly. Results This study included 102 patients (63.7% female) with a mean age of 62.3 ± 15.0 years. Patients with cardiomegaly (n = 64) had elevated BNP, BUN, and creatinine levels. They had elevated right atrial pressures, right ventricular pressures, and pulmonary artery pressures and reduced cardiac indices and reduced mixed venous oxygen saturations. There were no differences in echocardiographic parameters between the two groups. Conclusions This study demonstrates that the presence of cardiomegaly on chest radiographs has important clinical implications, including increased BNP levels and increased right heart pressures, in patients undergoing evaluation for pulmonary hypertension. Consequently, the presence of cardiomegaly supports the need for additional evaluation, including right heart catheterization, and provides useful information for primary care physicians and specialists.